2022
DOI: 10.3390/diagnostics12123052
|View full text |Cite
|
Sign up to set email alerts
|

p53 Modulates Radiosensitivity in Head and Neck Cancers—From Classic to Future Horizons

Abstract: p53, initially considered a tumor suppressor, has been the subject of research related to cancer treatment resistance in the last 30 years. The unfavorable response to multimodal therapy and the higher recurrence rate, despite an aggressive approach, make HNSCC a research topic of interest for improving therapeutic outcomes, even if it is only the sixth most common malignancy worldwide. New advances in molecular biology and genetics include the involvement of miRNA in the control of the p53 pathway, the unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 152 publications
0
2
0
Order By: Relevance
“…In the present study, p53 mutations were detected in 35.7% of the patients. Previous studies have suggested that HPV-negative tumors may be more resistant to definitive CRT due to an association between the p53 mutation and HPV-negative status (43)(44)(45)(46). Soares et al (32) detected p53 gene mutations in all HPV-negative cases and identified a significant association between poor treatment response at 6 months and the p53 mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, p53 mutations were detected in 35.7% of the patients. Previous studies have suggested that HPV-negative tumors may be more resistant to definitive CRT due to an association between the p53 mutation and HPV-negative status (43)(44)(45)(46). Soares et al (32) detected p53 gene mutations in all HPV-negative cases and identified a significant association between poor treatment response at 6 months and the p53 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The study targeted 15 high-risk HPV types, namely HPV 16,18,31,33,35,39,45,51,52,56,58,59, 66, 67 and 68, which were grouped into HPV 16, HPV 18 and other high-risk types. In the analysis phase, patients were categorized as HPV positive or HPV negative.…”
Section: Patientsmentioning
confidence: 99%